The Use of Euphemism on @Mahyartousi’s Twitter Comments: Sociolinguistics Perspective - Dwi, Niluh Kadek (Language Horizon: Journal of Language Studies, 2023)
Language is a simple way to communicate with other people and convey it not only verbally orally but also in writing. On the other hand, language can also be used to reveal a person's personality, therefore everyone needs to choose the right words to speak or write. This research uses a qualitative approach from the theory Creswell, 2014; Miles, Huberman, & Saldana (2014), Qualitative approach was chosen as the methodology to analyze the data findings because it is the most suitable method to answer the research questions. This study uses euphemisms to analyze the Reply comments in the Twitter account @MahyarTousi. in this study resulted in several conclusions where there were two types of each comment that fall into the type of euphemism (Irony and Presupposition) as well as on the existing social class aspects. This also correlates in euphemism in comments aimed at processing sentence style in insinuating a sentence that is indirectly aimed at sarcasm in euphemism sentences where there are the types of social classes including upper, lower, and middle in each category as an educated and uneducated classes.